Delegation of Authority from Dentists to Dental and Oral Therapists in Performing Medical Actions From a Legal Perspective - Ni Made Witari Dewi (Universitas Bali Dwipa, 2021)
Legal protection for the dental and oral therapist profession in carrying out medical actions is often less of a concern because in certain circumstances dental and oral therapists take actions that are not under their authority but are the authority of the dentist. Regulation of the Minister of Health Number 20 of 2016 concerning Permits and Implementation of the Practice of Dental and Oral Therapists, among others, regulates the competence and authority of dental and oral therapists in medical procedures. So the researchers focused on the problem, namely how is the delegation of authority from dentists to dental and oral therapists in carrying out medical actions? The method used in this study is a normative research method and the problem approach used is the applicable law approach and the conceptual approach. The results of the discussion found that the delegation of authority of dentists to dental and oral therapists in medical actions viewed from a legal perspective is that dentists can delegate a medical or dental action to nurses, midwives or certain other health workers in writing in carrying out medical or medical actions. tooth. This is clearly stated in Ministerial Regulation Number 2052 of 2011 concerning Practice Licenses and Implementation of Medical Practices. In Regulation of the Minister of Health Number 20 of 2016 concerning Permits and Implementation of Dental and Oral Therapist Practices, dental and oral therapists can carry out services under the supervision of a mandated delegation of authority from dentists. The two legal umbrellas can certainly make understanding and legal protection for dentists and dental and oral therapists in carrying out medical actions.